Answer:
a) The next three terms are -1,-3,-5,-7,-9,-11,-13
b) This is arithmetic sequence
C) The difference of second term and first term is -2 in given sequence so the given sequence is an arithmetic sequence.
d) The 27 th term is -53
Step-by-step explanation:
a) the given sequence is arithmetic sequence
the difference of second term and first term is -2
given sequence is -1,-3,-5,-7.....
the nth term in arithmetic sequence
![t_{n} = a+(n-1)d](https://tex.z-dn.net/?f=t_%7Bn%7D%20%3D%20a%2B%28n-1%29d)
First term is a = -1 and difference is d = -2
finding fifth term is
![t_{5} = -1 +(5-1)(-2)](https://tex.z-dn.net/?f=t_%7B5%7D%20%3D%20-1%20%2B%285-1%29%28-2%29)
![t_{5} = -1-8 =-9](https://tex.z-dn.net/?f=t_%7B5%7D%20%3D%20-1-8%20%3D-9)
finding sixth term is
![t_{6} = -1 +(6-1)(-2)](https://tex.z-dn.net/?f=t_%7B6%7D%20%3D%20-1%20%2B%286-1%29%28-2%29)
![t_{6} = -1-10 =-11](https://tex.z-dn.net/?f=t_%7B6%7D%20%3D%20-1-10%20%3D-11)
finding seventh term is
![t_{7} = -1 + (7-1)(-2)](https://tex.z-dn.net/?f=t_%7B7%7D%20%3D%20-1%20%2B%20%287-1%29%28-2%29)
![t_{7} = -1 -12 =-13](https://tex.z-dn.net/?f=t_%7B7%7D%20%3D%20-1%20-12%20%3D-13)
The next three terms are -9,-11,-13
The given sequence is -1,-3,-5,-7,-9,-11,-13
b) This is arithmetic sequence.
C) because the difference of second term and first term is -2 so the given sequence is arithmetic sequence.
d) by using nth term formula in arithmetic sequence
![t_{n} = a+(n-1)d](https://tex.z-dn.net/?f=t_%7Bn%7D%20%3D%20a%2B%28n-1%29d)
a= -1 and d =-2
<u>find 27 t h term :-</u>
<u></u>
<u></u>